1965
DOI: 10.1542/peds.36.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Snakebites in Children and Adults

Abstract: This study is based on the hospital records of 1,538 people bitten by poisonous snakes during 1958 and 1959 in 10 selected states having high snakebite rates. Of these, 792 were less than 20 years of age and 746 were 20 or more years of age. Snakebite rates were highest among children 5-19 years of age. Males had higher rates than females and whites had higher rates than non-whites. Children were not found to have excessively high case-fatality rates. Ninety-five percent of the sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…19,20 This study, as well as a companion study comparing snakebite in children to snakebite in adults, have been cited as recently as 2016, perhaps due to the lack of more recent epidemiologic studies using hospital and ED data. 4 ,10,11,19,21–24…”
Section: Discussionmentioning
confidence: 99%
“…19,20 This study, as well as a companion study comparing snakebite in children to snakebite in adults, have been cited as recently as 2016, perhaps due to the lack of more recent epidemiologic studies using hospital and ED data. 4 ,10,11,19,21–24…”
Section: Discussionmentioning
confidence: 99%
“…In adults, 85% of RSBs occur on the upper extremities, while in children, 70% occur to the lower extremities. [1][2][3][4][7][8][9][10][11][12] The percentage of upper extremity RSBs in adults correlates with a higher incidence of illegitimate bites and ethanol intoxication. 1,7,12 Weber and White 13 have suggested that children will sustain a more severe toxicity because of an increased venom:body mass ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, 85% of RSBs occur on the upper extremities, while in children, 70% occur to the lower extremities. 1 4,7 12 The percentage of upper extremity RSBs in adults correlates with a higher incidence of illegitimate bites and ethanol intoxication. 1,7,12…”
Section: Introductionmentioning
confidence: 99%
“…Children are often more vulnerable than adults to snakebite for multiple reasons. Their inquisitive nature and lack of personal restraint and/or awareness may render them at greater risk to envenomation [ 17 ]. For example, children in north-eastern South Africa being twice as likely to be envenomated as adults [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, children in north-eastern South Africa being twice as likely to be envenomated as adults [ 18 ]. In addition to frequency, severity of envenomation is often greater in children due to distances walked after the bite before treatment [ 17 ]. Furthermore, being physically smaller is likely to increase the severity of the medical emergency from snakebite envenomation due to relatively higher venom concentrations, i.e., a lower dilution effect in children during envenomation.…”
Section: Introductionmentioning
confidence: 99%